2021
DOI: 10.1017/s0003055421000642
|View full text |Cite
|
Sign up to set email alerts
|

Is Deliberation an Antidote to Extreme Partisan Polarization? Reflections on “America in One Room”

Abstract: This paper is positioned at the intersection of two literatures: partisan polarization and deliberative democracy. It analyzes results from a national field experiment in which more than 500 registered voters were brought together from around the country to deliberate in depth over a long weekend on five major issues facing the country. A pre–post control group was also asked the same questions. The deliberators showed large, depolarizing changes in their policy attitudes and large decreases in affective polar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
42
2
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(53 citation statements)
references
References 62 publications
3
42
2
6
Order By: Relevance
“…Of course, our studies only allow us to rule out the hypothesis that brief contact with an outpartisan would change attitudes toward democratic accountability. Our results do not speak to whether or not more sustained engagement or interventions with greater training and facilitation, such as which occurred in the America in One Room experiment ( 35 ), might lead to changes in political attitudes or behaviors. Future research may also wish to examine more sustained engagement (e.g., repeated interaction with outpartisans) as well as conversation prompts, which more explicitly elicit discussion of political elites or democratic norms.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Of course, our studies only allow us to rule out the hypothesis that brief contact with an outpartisan would change attitudes toward democratic accountability. Our results do not speak to whether or not more sustained engagement or interventions with greater training and facilitation, such as which occurred in the America in One Room experiment ( 35 ), might lead to changes in political attitudes or behaviors. Future research may also wish to examine more sustained engagement (e.g., repeated interaction with outpartisans) as well as conversation prompts, which more explicitly elicit discussion of political elites or democratic norms.…”
Section: Discussioncontrasting
confidence: 56%
“…Might different approaches to fostering deliberation [e.g., ( 40 )] produce longer-lasting effects? Or might more sustained engagement or the presence of a skilled moderator do so ( 35 )? Such questions about whether it is possible to instruct laypeople to have more productive cross-partisan conversations than they are by default remain a question for future research.…”
Section: Discussionmentioning
confidence: 99%
“…This pattern suggests that respondents in conversations with explicit partisan labels may more easily draw connections between the conversation and existing partisan stereotypes, experiences, and attitudes-a necessary precondition for attitudinal change. This finding is consistent with recent research that finds polarization is fueled by wildly overestimated partisan stereotypes (Levendusky and Malhotra, 2016;Ahler and Sood, 2018;Moore-Berg et al, 2020;Paluck et al, 2019;Enders and Armaly, 2019;Ruggeri et al, 2021), so that a conversation with a member of the other party that contradicts prevailing stereotypesrevealing the actual extent of heterogeneity in partisan views-should help to depolarize Fishkin et al, 2021;Wojcieszak and Warner, 2020;Druckman et al, 2021b). It is telling that this is the case whether a respondent is told they are talking to someone from their outgroup or ingroup-consistent with recent research finding that ingroup social pressures contribute to polarization (White and Laird, 2020).…”
Section: Discussionsupporting
confidence: 90%
“…For instance, recent work concludes that Facebook use may increase political polarization (Settle, 2018) and exposure to ideologically uncongenial information can push partisans further apart (Bail et al, 2018). However, other research suggests that people will moderate their views when they engage with those with different perspectives because they come to recognize the value of alternative viewpoints (Fishkin and Luskin, 2005;Mutz, 2006;Zhang, 2019;Broockman and Kalla, 2016;Fishkin et al, 2021). For example, recent studies have found significant reductions in partisan animosity from engaging in cross-party conversations in-person Fishkin et al, 2021), on video chat (Santoro and Broockman, 2022), and over text .…”
Section: Introductionmentioning
confidence: 99%
“…A divided citizenry makes confronting democratic problems harder, as it reduces a shared sense of group goals that underscore democratic legitimacy. There is a large literature aimed at rebuilding intergroup trust, using tools like interparty contact and deliberation to de-escalate polarization (Fishkin et al 2021). These are promising exercises, and it follows that increased cooperation outside of partisan silos may increase a shared sense of civic obligation and group goals.…”
Section: Discussionmentioning
confidence: 99%